Attributable risk of suicide for populations in Australia - Bandara, Piumee; Page, Andrew; Reifels, Lennart; Krysinska, Karolina; Andriessen, Karl; Schlichthorst, Marisa; Flego, Anna; Le, Long Khanh-Dao; Mihalopoulos, Cathrine; Pirkis, Jane (Frontiers in Psychiatry, 2024)
Objective Each year approximately 3,000 Australians die by suicide. We estimated the population attributable risk for identified target populations to provide evidence on how much of the overall burden of suicide in the Australian population is experienced by each of them. Methods We identified 17 demographic and clinical target populations at risk of suicide and calculated the population attributable fraction (PAF) using a single or pooled suicide risk and the proportional representation of each target population within Australia. Results Large PAF estimates were found for men (52%, 95% confidence interval (CI) 51%–53%), people bereaved by suicide (35%, 95% CI 14%–64%), people with a mental health or behavioural condition (33%, 95%CI 17%–48%), people with a chronic physical condition (27%, 95%CI 18%–35%), adults aged 25–64 years (13%, 95%CI 12%–14%), LGB populations (9%, 95%CI 6%–13%), offenders (9%, 95%CI 8%–10%), and people employed in blue collar occupations (8%, 95%CI 4%–12%). Limitations The PAF is limited by assumptions, namely, that risk factors are independent, and that the relationship between risk factors and outcomes are unidirectional and constant through time. Conclusions and implications for public health Considerable reductions in the overall suicide rate in Australia may occur if risk factors are addressed in identified populations with large PAF estimates. These estimates should be considered as an adjunct to other important inputs into suicide prevention policy priorities.